Dochnahl's pomological books and their relevance for botanical nomenclature. Issue 2 (3rd April 2016) - Greuter, Werner; Holstein, Norbert
Abstract: Biographical data are presented on Friedrich Jakob Dochnahl (1820–1904), a once prominent but long forgotten German pomologist. Two among his scientific works, the "New pomological system" of 1847 and the four‐volume "Secure guide in pomology" (1855–1860), being of interest for nomenclatural purposes, are presented and discussed in detail. The former includes 16 so far overlooked species names, none of which affects any name in current use. In the latter, 143 generic names and over 4000 species names are validly published, all of them completely ignored to date. In a corollary paper, suppression of that work is being proposed.